2017
DOI: 10.1007/978-3-319-50520-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Helicobacter pylori Replication: Possible Implications in Adaptation to a Pathogenic Lifestyle and Perspectives for Drug Design

Abstract: DNA replication is an important step in the life cycle of every cell that ensures the continuous flow of genetic information from one generation to the next. In all organisms, chromosome replication must be coordinated with overall cell growth. Helicobacter pylori growth strongly depends on its interaction with the host, particularly with the gastric epithelium. Moreover, H. pylori actively searches for an optimal microniche within a stomach, and it has been shown that not every microniche equally supports gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 171 publications
0
6
0
Order By: Relevance
“…The DnaA boxes insensitive to the DNA topology (classic (c) boxes) and the topology‐sensitive (ts) DnaA boxes and DUE are marked. See also the Introduction and (Donczew et al, ; Zawilak‐Pawlik & Zakrzewska‐Czerwińska, ) for details. (b–d) Sensograms presenting the DnaA– oriC1 interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The DnaA boxes insensitive to the DNA topology (classic (c) boxes) and the topology‐sensitive (ts) DnaA boxes and DUE are marked. See also the Introduction and (Donczew et al, ; Zawilak‐Pawlik & Zakrzewska‐Czerwińska, ) for details. (b–d) Sensograms presenting the DnaA– oriC1 interactions.…”
Section: Resultsmentioning
confidence: 99%
“…H. pylori has established itself as an efficient bacterium owing to its quick adaptation in areas such as the stomach and duodenum, and various mutated strains were found to be living in the gastric area [78]. H. pylori has shown that it has vast genetic diversity, starting from genetic mosaicism to polymorphisms of nucleotides; this was found through analysis of its genome [79].…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…It is well established that H. pylori is a highly competent bacterium, and different strains can be found living together in the gastric environment, bringing the populations of H. pylori closer to panmixia (Kang & Blaser, 2006; Suerbaum et al, 1998). Genome comparative analyses from diverse origins have shown that this bacterium shows a high degree of genetic diversity, ranging from nucleotide polymorphisms to genetic mosaicism (Zawilak-Pawlik & Zakrzewska-Czerwińska, 2017).…”
Section: Introductionmentioning
confidence: 99%